A Novel BER Analytical Performance Of DWT Based OFDM Using Various Channel Over DFT Based OFDM (International Journal of Engineering and Computer Science, 2015)
OFDM has been widely adopted in many applications due to its good spectral performance and low sensitivity to impulse noise and multipath channels. In OFDM that a cyclic prefixes (CP) is appended to each symbol in order to mitigate the effect of Inter-Symbol-Interference (ISI) and inter carrier interference (ICI). However, this reduces the spectral efficiency. A perfect reconstruction using wavelet based OFDM provides good orthogonality and with its use Bit Error Rate is improved. Wavelet based system does not require CP, so spectrum efficiency is increased. In this paper, we are presenting BER analysis of conventional and wavelet based OFDM in LTE using different modulation techniques like QAM 2, QAM 4, QAM 16, QAM 256 and PSK.